Saucer : the conquest - Coonts, Stephen, 1946- (New York : St. Martin's Griffin, 2004)
Seismic surveyor Rip Cantrell and beautiful test pilot Charley Pine, having safely delivered the 140,000-year-old flying saucer Rip uncovered in the Sahara desert to the Smithsonian, believe their days of adventure are over, but they soon find themselves having to steal the saucer back when Charley discovers a world-threatening antigravity beam, and Rip's uncle is kidnapped.
Sequel to: Saucer.
Publisher's Weekly
Adult.
Adult
Keywords: Space flight -- Fiction; Space ships -- Fiction; Unidentified flying objects -- Fiction; Adventure fiction; Science fiction; Space flight -- Fiction; Space vehicles -- Fiction; Unidentified flying objects -- Fiction; Nevada -- Fiction; Nevada -- Fiction; Science fiction; Suspense fiction